The faster you decide, the more accurate localization is possible: Position representation of "curveball illusion" in perception and eye movements. - Hiroshi Ueda; Naotoshi Abekawa; Hiroaki Gomi (PLoS ONE, 2018)
When the inside texture of a moving object moves, the perceived motion of the object is often distorted toward the direction of the texture's motion (motion-induced position shift), and such perceptual distortion accumulates while the object is watched, causing what is known as the curveball illusion. In a recent study, however, the accumulation of the position error was not observed in saccadic eye movements. Here, we examined whether the position of the illusory object is represented independently in the perceptual and saccadic systems. In the experiments, the stimulus of the curveball illusion was adopted to examine the temporal change in the position representation for saccadic eye movements and for perception by varying the elapsed time from the input of visual information to saccade onset and perceptual judgment, respectively. The results showed that the temporal accumulation of the motion-induced position shift is observed not only in perception but also in saccadic eye movements. In the saccade tasks, the landing positions of saccades gradually shifted to the illusory perceived position as the elapsed time from the target offset to the saccade "go" signal increased. Furthermore, in the perception task, shortening the time between the target offset and the perceptual judgment reduced the size of the illusion effect. Therefore, these results argue against the idea of dissociation between saccadic and perceptual localization of a moving object suggested in the previous study, in which saccades were measured in a rushed way while perceptual responses were measured without time constraint. Instead, the similar temporal trends of these effects imply a common or similar target representation for perception and eye movements which dynamically changes over the course of evidence accumulation.